2007
DOI: 10.1523/jneurosci.0013-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Vesicular Glutamate Transporter 1 Function and Expression Related to Methamphetamine-Induced Glutamate Release

Abstract: The vesicular glutamate (GLU) transporter (VGLUT1) is a critical component of glutamatergic neurons that regulates GLU release. Despite the likely role of GLU release in drug abuse pathology, there is no information that links VGLUT1 with drugs of abuse. This study provides the first evidence that methamphetamine (METH) alters the dynamic regulation of striatal VGLUT1 function and expression through a polysynaptic pathway. METH increases cortical VGLUT1 mRNA, striatal VGLUT1 protein in subcellular fractions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 43 publications
(49 reference statements)
1
60
0
Order By: Relevance
“…Indeed, there is evidence that glutamate signaling itself is capable of modifying transcriptional regulation and expression, notably in the context of brain injury (46). VGLUT expression is regulated in other brain regions in response to seizures, hypoxia, stress, methamphetamine, antidepressants or in PD (47)(48)(49)(50)(51)(52). Remarkably, we saw an approximate doubling in the fraction of DA neurons labeled for VGLUT2 following a striatal 6-OHDA injection.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, there is evidence that glutamate signaling itself is capable of modifying transcriptional regulation and expression, notably in the context of brain injury (46). VGLUT expression is regulated in other brain regions in response to seizures, hypoxia, stress, methamphetamine, antidepressants or in PD (47)(48)(49)(50)(51)(52). Remarkably, we saw an approximate doubling in the fraction of DA neurons labeled for VGLUT2 following a striatal 6-OHDA injection.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, the greater glutamate extraction fraction exhibited by METH-SA animals primarily reflected greater gains in perfusate glutamate at concentrations below, rather than above, y ¼ 0. Although a body of data derived from studies of non-contingent methamphetamine models have indicated elevated striatal glutamate clearance following neurotoxic dosing regiments (Mark et al, 2007;Nishino et al, 1996;Shirai et al, 1996), our in vivo data suggest enhanced basal glutamate release, most probably from extra-synaptic sources given the nature of microdialysis, as at least one mechanism to account for the elevated basal NAC glutamate levels observed in METH-SA animals (see Bungay et al, 2003;Chefer et al, 2006;Parsons and Justice, 1994 for detailed discussion). This being said, METH-NC animals also exhibited elevated basal glutamate but failed to exhibit drug-induced changes in the extraction fraction.…”
Section: Possible Mediators Of Changes In Nac Glutamate Produced By Cmentioning
confidence: 64%
“…The pathway by which METH causes dopaminergic neurotoxicity shares similarities with other neurodegenerative pathways, including the GAPDH-Siah pathway (3)(4)(5), which is activated in both animals and cells by the Parkinson disease-inducing agent, 1-methyl-4-phelyl-1,2,3,6,-tetrahydropyridine (MPTP) (18). Together with the observation that METH causes an increase in striatal GAPDH protein levels (19), these findings led us to the hypothesis that GAPDH might participate in the METH neurotoxicity pathway.…”
Section: Glyceraldehyde-3-phosphate Dehydrogenase (Gapdh)mentioning
confidence: 85%